SVIFT - The Svalbard ice-free topography - Fürst, Johannes J. (Norwegian Polar Institute, 2018)
We present an ice-free (bedrock) topography of the Svalbard archipelago based on a two-step mass-conserving approach for mapping glacier ice thickness. The Svalbard-wide application is presented in Fürst et al. (2018) and details of the mass-conserving reconstruction approach are specified in Fürst et al. (2017). For the thickness reconstruction more than one million individual measurements were considered. The map is provided together with an error-estimate field, which provides first spatial information on the reliability of the reconstruction.